Using RNA-based therapies to target the kidney in cardiovascular disease - Palmer, Trecia C.; Hunter, Robert W. (Frontiers in Cardiovascular Medicine, 2023)
RNA-based therapies are currently used for immunisation against infections and to treat metabolic diseases. They can modulate gene expression in immune cells and hepatocytes, but their use in other cell types has been limited by an inability to selectively target specific tissues. Potential solutions to this targeting problem involve packaging therapeutic RNA molecules into delivery vehicles that are preferentially delivered to cells of interest. In this review, we consider why the kidney is a desirable target for RNA-based therapies in cardiovascular disease and discuss how such therapy could be delivered. Because the kidney plays a central role in maintaining cardiovascular homeostasis, many extant drugs used for preventing cardiovascular disease act predominantly on renal tubular cells. Moreover, kidney disease is a major independent risk factor for cardiovascular disease and a global health problem. Chronic kidney disease is projected to become the fifth leading cause of death by 2040, with around half of affected individuals dying from cardiovascular disease. The most promising strategies for delivering therapeutic RNA selectively to kidney cells make use of synthetic polymers and engineered extracellular vesicles to deliver an RNA cargo. Future research should focus on establishing the safety of these novel delivery platforms in humans, on developing palatable routes of administration and on prioritising the gene targets that are likely to have the biggest impact in cardiovascular disease.